Water permeability study of NafionÂ® 117 membrane after undergoing hot press - Kadhum, Abdul Amir H.; Mohamad, Abu Bakar; Wan Daud, Wan Ramli; Harahap, Navriani; Sitanggang, Ramli (2004)
Influence of various hot press treatment on Electrode Assembly (MEA) fabrication was investigated. The correlation between press and water permeability through both side of electrode was observed also. The hot press with temperature at 130oC was found to be more relevant to produce a more pore sizes in the catalyst layer and supporting higher surface area. The hot press temperature of 130Â°C was observed to develop a better pores spaces. The MEA produced was analyzed for water flux test and porosity of membrane at various of temperature was investigated also. The balance between the hot press temperature and the pressure will allow the right amount of water to exit the electrode thus making the electrode more resistant, with better efficiently and long lasting.